Hydrogen desorption from alloys Mg–Cu(–KCl): Cu catalysis in detail. (19th April 2021) - Cermak, Jiri; Kral, Lubomir; Roupcova, Pavla
Abstract: Effect of chemical composition of Mg- x Cu based alloys ( x  = 9.94–58.00 wt %) modified by KCl upon their hydrogen storage performance was studied. Kinetic curves and pressure-concentration isotherms were measured in the ranges up to 60 bar and 388 °C, respectively. It was observed that desorption rate d c /d t is not significantly influenced by the composition. Unknown Cu-rich phase was detected that has shown a catalytic effect on desorption from a mixture with other phases. Activation energy of hydrogen desorption decreased with increasing x from 180 kJ/mol down to 98 kJ/mol. Average hydride dissociation enthalpy, Δ H, for the lowest plateau was 75 kJ/mol which is equal to literature value for pure Mg. Slightly lover average value, 67 kJ/mol was obtained for the second plateau and Δ H for the third one decreased from 70 kJ/mol for the lowest to 49 kJ/mol for the highest x . Highlights: Unknown Cu-rich phase UP was observed, with low sorption capacity c max and low Δ H. Hydrided UP enables to reach higher values of total c max . Hydride dissociation enthalpy Δ H decreases with increasing Cu concentration c Cu . d c /d t is unaffected by c Cu . Activation energy of desorption E a decreases with increasing c Cu .